California County Planning Association Conference at Lake Arrowhead - Watkins, Howard::::::::: (1984)
Association's Secretary-Treasurer Marjorie Shields (Tulare) and Immediate Past-President Jack Lish (Placer) at lectern Association President Russ Easterday (San Bernardino) in background